Collaborative Approach: "Chemistry Goes to School" To Increase Interest in Studying Chemistry in High School (Based on Main Higher Education Work Indicators): Pendekatan Kolaboratif: "Chemistry Goes to School" Untuk Meningkatkan Minat Belajar Kimia di SMA (Berbasis Indikator Kerja Utama Perguruan Tinggi) - Dewi KA. Kusumahastuti; Margareta N. Cahyanti; Tirza W. Brotosudarmo; Jose DM. Yonggulemba; Sri Hartini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
"Chemistry Goes to School" is an educational program that aims to introduce basic chemistry concepts to students in an interesting and interactive way. This program is designed not only based on Key Performance Indicators (KPIs) for Higher Education but also to educate students about the principles of chemistry in everyday life and inspire their interest in the field of chemistry. The implemented program components include (a) interactive scientific discussions with professors from abroad, (b) interactive chemistry games and (c) exhibition of lecturers' and students' research results. The "Chemistry Goes to School" program is expected to be able to change students' view of chemistry from something complicated to something interesting and relevant in their daily lives. With an interactive and varied approach, it is hoped that students will feel more involved and motivated in learning chemistry. The feedback from this activity was that the students were very enthusiastic, and this activity was very useful. The input from this activity is that similar activities are to be carried out periodically in schools.